Analysis and testing on the interference due to atmospheric duct of 5G - Xingang SONG; Xingzheng LI; Zhimin ZHAO; Yan WANG (Dianxin kexue)
Abstact: 5G (time division duplexing, TDD) system will be effected by the interference from 5G system due to atmospheric duct.The risk and current situation of 5G system in 2.6 GHz band were introduced and the interference characteristics of 5G interference due to atmospheric duct were summarized.Then based on the interference test results of the interference from 5G system due to atmospheric duct, the interference due to atmospheric duct influences under different frame offset, different service load and different antenna dip configuration were analyzed.Finally, the suggestions for the optimization of 5G interference due to atmospheric duct in 2.6 GHz band were obtained.